PROSEDUR AUDIT ATAS PIUTANG USAHA PADA PT X OLEH KAP BCA - Selomitha Soffi, Auni Bhetrisia; Budiwitjaksono, Gideon Setyo (STIE Mahardhika, 2025)
This study aims to assess the effectiveness of the audit procedures on accounts receivable conducted by the Public Accounting Firm (KAP) BCA for PT X, a trading company with high sales volume. In addition, this research also evaluates the extent to which the company's internal control system can minimize the risk of uncollectible accounts and identifies the factors causing them. The method used is qualitative descriptive research with a field study approach conducted during the internship at KAP BCA. Data collection techniques include direct observation, interviews with auditors, audit documentation, and relevant literature studies. The audit procedures analyzed include examination of supporting documents, confirmations with third parties, and assessment of management policies related to receivables management. The advantage of this research lies in the utilization of internship experience as the primary data source, which provides real insights into the implementation of audits in the field. The research results show that all stages of the audit have been carried out thoroughly in accordance with the financial accounting standards in Indonesia. Based on the audit results, the presentation of accounts receivable for PT X is deemed reasonable and has adhered to generally accepted accounting principles.